2004
DOI: 10.2170/jjphysiol.54.53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperthermia on Ventilation and Metabolism during Hypoxia in Conscious Mice

Abstract: It has been reported that hyperthermia associated with fever and heat stroke may lead to apnea and death [1], and that elevated body temperature (BT) is recorded after death in sudden infant death syndrome [2]. Thus hyperthermia is an important risk factor for cardiorespiratory disorders. Here we are concerned with hyperthermia in respect to the control of ventilation and metabolism.Thermal effects on breathing patterns have been examined by artificially increasing BT under anesthesia. The increased BT affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The response to hypoxia has also been shown to depend on the end-tidal partial pressure of carbon dioxide (PET CO 2 ) (27). Hyperthermia in resting mice elevates their HVR (14), but what has not been examined in humans is whether the concomitant increase in core temperature evident with exercise has an influence on the ventilatory response to hypoxia. To this end, we have implemented an underwater exercise method, similar to that by Park and colleagues (24) to prevent increases in core temperature during exercise.…”
mentioning
confidence: 99%
“…The response to hypoxia has also been shown to depend on the end-tidal partial pressure of carbon dioxide (PET CO 2 ) (27). Hyperthermia in resting mice elevates their HVR (14), but what has not been examined in humans is whether the concomitant increase in core temperature evident with exercise has an influence on the ventilatory response to hypoxia. To this end, we have implemented an underwater exercise method, similar to that by Park and colleagues (24) to prevent increases in core temperature during exercise.…”
mentioning
confidence: 99%
“…In this condition, air was perfused for 30 min, and then hypoxic gas (7% O2 ϩ 3% CO2 balanced in N2) was perfused for 20 min. Hypoxic gas contained 3% CO2 to compensate for the reduction in arterial PO2 caused by "blowing off" of CO2 during elevated ventilation associated with hypoxia (16,33). Tests for hypoxic gas exposure were performed in light and dark periods.…”
mentioning
confidence: 99%
“…The HVD is most likely involved in hypocapnia following an initial increase in poikilocapnic hypoxia. Our previous study of blood gas analyses in mice revealed that PaCO 2 levels are strictly limited in poikilocapnic hypoxia [10] compared to normocapnic hypoxia [4,10] at 10 min after each hypoxic gas inhalation. Hypocapnia is more significant during the dark period than during the light because the initial increase is augmented during the dark period.…”
Section: Ve (Ml/min/10g Bw)mentioning
confidence: 96%
“…We added 3% CO 2 to the hypoxic gas to maintain a constant level of arterial PCO 2 (PaCO 2 ) [2,4,7]; this prevents hypocapnia induced by hypoxic hyperventilation [8]. Indeed, our previous blood gas analyses in mice showed PaCO 2 levels of 36-39 mmHg at 10 min after 7% O 2 inhalation adding 3% CO 2 [4, 9], but 19 mmHg at the same time after 7% O 2 inhalation [10]. However, hypoxic gas inhalation adding 3% CO 2 , augments the initial increase because of the activation of the chemoreceptor afferents responsible for changes in both PaO 2 and PaCO 2 [11].…”
mentioning
confidence: 99%